A Level Set-Discrete Element Method in YADE for numerical, micro-scale, geomechanics with refined grain shapes - Duriez, Jérôme; Galusinski, Cédric (Computers & geosciences, 2021)
A C++-Python package is proposed for 3D mechanical simulations of granular geomaterials, seen as a collection of particles being in contact interaction one with another while showing complex grain shapes. Following the so-called Level Set-Discrete Element Method (LS-DEM), the simulation workflow stems from a discrete field for the signed distance function to every particle, with its zero-level set corresponding to a particle’s surface. A Fast Marching Method is proposed to construct such a distance field for a wide class of surfaces. In connection with dedicated contact algorithms and Paraview visualization procedures, this shape description eventually extends the YADE platform for discrete simulations. Its versatility is illustrated on superquadric particles i.e. superellipsoids. On computational aspects, memory requirements possibly exceed one megabyte (MB) per particle when using a double numeric precision, and time costs, though also significant, appear to be lighter than the use of convex polyhedra and can be drastically reduced using a simple, OpenMP, parallel execution. [Display omitted] •A level-set particle description extends the YADE code for discrete mechanics.•It relies upon a discrete distance field and surface nodes for every particle.•Complex shapes can be described starting from a general Fast Marching Method.•The approach is memory-intensive but possibly much faster than the use of polyhedra.